2018
DOI: 10.7287/peerj.preprints.27375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What are the determinants of subjective well-being of healthy adults in rural communities in and around forests?

Abstract: Sustainability goals are seeking to jointly improve environmental conditions and the well-being of society. Yet achieving both environmental and human well-being goals remains challenging because improving the material well-being of people can often mean increasing the risk of environmental and ecosystem degradation. An alternative method that may help meet both goals is to target non-monetary determinants of subjective well-being. However. few studies have examined the determinants of subjective well-being in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2), and communities are engaged in agricultural activities throughout the year. For more on the study setting and population see Aggraeni et al 72 and Masuda et al 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), and communities are engaged in agricultural activities throughout the year. For more on the study setting and population see Aggraeni et al 72 and Masuda et al 9 .…”
Section: Methodsmentioning
confidence: 99%
“…Participants are, on average, 42 years old, have 6.3 years of education, live in households that consist of ∼4-5 members, and 83% and 73% are farmers and regularly work in forests, respectively. Further information about participants and the study population can be found in Supplementary Table 1 and Aggraeni et al 72 and Masuda et al 9 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other, having good health was also key in enabling people to not have stress, to have confidence in themselves, or critically, to engage in social relations, particularly because they could both welcome visitors at home and physically visit friends and relatives. This points to a broader positive impact of having good health on emotional and psychological well-being aspects, as has been found in developed and developing contexts alike (Chin, 2010;Aggraeni et al, 2018).…”
Section: The Bundled Nature Of Well-being Componentsmentioning
confidence: 58%